Spatiotemporal Patterns, Typology and Survival Analysis of Cyber Incidents in Brazil - Rodrigues, Gabriel Arquelau Pimenta; Oliveira, Matheus Noschang de; Serrano, André Luiz Marques; Lemos, Amanda Nunes Lopes Espiñeira; Santos, Evanei Gomes dos; Rocha Filho, Geraldo Pereira; Mendonça, Fábio Lúcio Lopes de; Silva, Daniel Alves da; Gonçalves, Vinícius Pereira (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2025)
Cyber incidents, such as data breaches, ransomware attacks and vulnerability exploitations, are consistently impacting Brazil. This study analyzes 1249 cyber incident reported to the Brazilian National Data Protection Authority from 2021 to 2025. We identify São Paulo and the Federal District as the most targeted states, with ransomware being the most prevalent attack type. The Kaplan-Meier survival analysis reveals rapid incident recurrence in major regions and of certain types of incidents, such as ransomware, vulnerable systems and credential theft. This study provides a foundational overview of Brazil’s cybersecurity scenario. The findings emphasize the importance of enhancing incident reporting and of improving proactive defenses.